Did bubbles migrate from the stock to the housing market in China between 2005 and 2010?. (August 2017) - Deng, Yongheng; Girardin, Eric; Joyeux, Roselyne; Shi, Shuping
Abstract: The speculative nature of both stock and housing markets in China has attracted the attention of observers. However, while stock market data are easily available, the low frequency and low quality of publicly available housing price data hampers the study of the relationship between the two markets. We use original hedonic weekly resale housing prices of a major Chinese housing market and study them in conjunction with Shanghai's stock market index in the second half of the 2000s. The use of the Phillips et al. (2015 a, b) recursive explosive‐root test enables us to detect and date speculative episodes in both markets. We then implement the Greenaway‐McGrevy and Phillips (2016) methodology to detect the presence of migration between the two types of bubbles. We detect significant migration from the stock to the housing market bubble in 2009 and a temporary spillover in 2007.